2022
DOI: 10.5603/dk.a2022.0024
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Resilience, Self-efficacy and Illness Perception in Patients with Type 2 Diabetes: A Cross-Sectional Study

Abstract: Background: The present study aims to investigate the correlation between resilience, self-efficacy, and illness perception in patients with type 2 diabetes mellitus in the south of Iran. Materials and methods: The present study is a crosssectional work conducted on 405 patients with type 2 diabetes mellitus who were selected via convenience sampling from clinics in the south of Iran, from December 2019 to July 2020. Data were collected using a questionnaire consisting of four sections: a demographics survey, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This is consistent with the findings of earlier research, which indicate that higher levels of psychological distress are associated with lower levels of resilience [ 12 ]. In different situations or when being exposed to risk factors, resilience helps patients solve their problems and cope better [ 46 ]. Resilience theory highlights that stressful conditions can decrease an individual’s Resilience, which may, in turn, jeopardize his/her physical and mental health [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of earlier research, which indicate that higher levels of psychological distress are associated with lower levels of resilience [ 12 ]. In different situations or when being exposed to risk factors, resilience helps patients solve their problems and cope better [ 46 ]. Resilience theory highlights that stressful conditions can decrease an individual’s Resilience, which may, in turn, jeopardize his/her physical and mental health [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on CAD patients, Barham et al reported that the self-efficacy score was 34, which this score was at a moderate level according to the number of questions and rating scales (Barham et al, 2019). Illness perception can be effective in improving self-efficacy in chronic diseases (Mohammadi et al, 2022). The results of Mohammadi et al's study also confirm this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Mohammadi et al's study also confirm this relationship. They showed a significant and positive relationship between illness perception and self-efficacy in patients with type 2 diabetes, that is, patients with a greater perception of illness conditions, including the effect of the disease on their lives, had more abilities in performing activities related to self-efficacy and disease management (Mohammadi et al, 2022). However, Knowles et al found a significant but negative relationship between these two variables (Knowles et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations